La jurisdicción marítima en Colombia (2008)
The present work has as purpose to analyze who is the marine authority in Colombia and which is the artificial nature of its shortcomings. Specifically The specific objectives are: To study the normative evolution of the marine jurisdiction in Colombia, to analyze the artificial structure of the national marine authority, to know the applicable procedure to the investigations that it advances the national marine authority with respect to the marine conflicts especially those considered accidents and marine catastrophes and to Investigate on the artificial nature of the shortcomings of the national marine authority. This study is of descriptive character, since in the one that you/they are selected a series of positions in independent way of all the concepts here mentioned, of equal he/she is formed it seeks to describe and to analyze the legal budgets of the marine jurisdiction in Colombia. In conclusion, The jurisdiction marine Colombian is in head of the marine General Address DIMAR that although it shows the condition of an administrative authority, it exercises in form exceptional judicial functions for expressed command of the article 5º, numeral 27 of the Ordinance Law 2324 of 1984, norm that gathers the requirements that it demands the article 116 of the Political Constitution for the effect. The jurisdictional abilities of the DIMAR don't extend to all their investigations.